Use of coils for transcatheter carotid occlusion. - Braun, I F; Hoffman, J C; Casarella, W J; Davis, P C (American Journal of Neuroradiology, 1985)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf